ANALISIS PEMASARAN BERAS DI KECAMATAN SIDOREJO KOTA SALATIGA - Ria Rosdiana Silaban; Yuliawati Yuliawati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
This study aims to determine the pattern of rice marketing channels, the margin of each institution, and the efficiency of rice marketing channels. Descriptive quantitative research methods. By collecting data determined by purposive sampling through observation and interviews using a questionnaire using 30 samples of rice farmers respondents. Samples for rice marketing channel patterns use snowball sampling techniques. The analytical methods used are marketing margin analysts, marketing channel profits, farmer's share and efficient marketing. The results showed that there were three patterns of rice marketing channels, namely: channel I: Farmers - Brokers - Retailers - Consumers; channel II: Farmers - Rice Grinders - Retailers - Consumers; channel III: Farmers - Gapoktan - Retailers - Consumer. Margin of trading channel I farmers to Pandan Wangi rice middlemen Rp 6,400 / kg, IR64 Rp 4,800 / kg, middlemen to Pandan wangi rice retailers Rp 600 / kg, IR64 Rp 1,000 / kg; Channel II grinder to Pandan Wangi farmers Rp 6,700 / kg, IR64 Rp 4,800 / kg, grinder to Pandan wangi commodity retailer Rp 500 / kg, IR64 Rp 1,200 / kg; Channel III Gapoktan to Pandan Wangi rice farmers Rp.6,500 / kg, IR64 Rp 4,500 / kg, Gapoktan to Pandan wangi rice retailers Rp 500 / kg, IR64 Rp 1,200 / kg. The highest farmer share value was found in channel III Pandan Fragrant 48%, IR64 54%. The most efficient marketing of the three channels is in channel III Pandan Fragrant 13% IR64 16%.